2021
DOI: 10.1016/j.bbrep.2021.100996
|View full text |Cite
|
Sign up to set email alerts
|

miR-33a-5p in small extracellular vesicles as non-invasive biomarker for oxaliplatin sensitivity in human colorectal cancer cells

Abstract: microRNAs (miRNAs) contained in small extracellular vesicles (sEVs) are candidates for non-invasive biomarkers. Oxaliplatin (L-OHP) has been approved for advanced colorectal cancer (CRC) chemotherapy. However, the response to L-OHP differs among CRC patients. In addition, CRC cells often acquire the resistance to L-OHP. This study aimed at the prediction of L-OHP sensitivity by measuring extracellular miRNAs levels. Firstly, we compared intracellular miRNAs expressions in L-OHP-sensitive CRC cells (SW620 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…More specifically, ex-miR-200c and ex-miR-141 were suggested as potential biomarkers for mesenchymal-epithelial transition of oxaliplatin-resistant CRC cells [74] while the exosomal expression level of let-7b was associated with the cells' invasion activity [75]. Last, but not least, another work by the same authors reported that the downregulation of miR-33a-5p and miR-210-3p is correlated with oxaliplatin resistance; a possible explanation implicates the inhibition of several genes related with DNA damage repair mechanisms [76].…”
Section: Exosomal Mirnas and Crc Drug Resistancementioning
confidence: 98%
“…More specifically, ex-miR-200c and ex-miR-141 were suggested as potential biomarkers for mesenchymal-epithelial transition of oxaliplatin-resistant CRC cells [74] while the exosomal expression level of let-7b was associated with the cells' invasion activity [75]. Last, but not least, another work by the same authors reported that the downregulation of miR-33a-5p and miR-210-3p is correlated with oxaliplatin resistance; a possible explanation implicates the inhibition of several genes related with DNA damage repair mechanisms [76].…”
Section: Exosomal Mirnas and Crc Drug Resistancementioning
confidence: 98%
“…Exosomal miRNAs may act as chemoresistance regulators and anticipate poor results in CRC patients. Shota Tanaka et al found that acquired and intrinsic L-OHP-resistant CRC cells had lower expression of miR-33a-5p and/or miR-210-3p than sensitive cells, suggesting that miR-33a-5p would be a candidate biomarker of L-OHP sensitivity [ 135 ]. In another study, exosomal miR-208b was related to a decrease in oxaliplatin-based chemosensitivity in CRC, as it promotes Treg proliferation by targeting PDCD4 [ 136 ].…”
Section: Main Textmentioning
confidence: 99%
“…As mentioned above, most radiation-modulating natural-product-regulated miRNAs (Table 3) are associated with exosome biogenesis and miRDB results for exosome biogenesismodulating targets. However, other miRNAs , such as miR-3960 [143], miR-6085 [144], miR-18a-5p [145], miR-22-3p [146], miR-126-3p [147], miR-137-3p [148], miR-122-5p [149], miR-23a-3p [150], miR-155-5p [151], miR-33a-5p [152], miR-574-3p [153], miR-132-3p [154], miR-211-5p [155], miR-375-3p [156], miR-181c-3p [157], miR-146a-5p [158], miR-542-3p [159], miR-877-3p [160], miR-192-5p [161], miR-451a [162], miR-215-5p [163], miR-99b-3p [164], miR-549a-5p [165], and miR-1247-5p [166], have only been reported in terms of exosome biogenesis-modulating effects, without available miRDB results for exosome biogenesis-modulating targets.…”
Section: Other Natural-product-regulated Mirnas May Have Exosome Biog...mentioning
confidence: 99%
“…miR-33a-5p was underexpressed in oxaliplatin-resistant colon cancer cells compared to sensitive control cells. Exosomal miR-33a-5p was present at only a low level in resistant colon cancer cells [152]. Placenta-derived exosomal miR-574-3p was underexpressed after chemerin, enhancing proliferation and angiogenesis for gestational diabetes mellitus [153].…”
Section: Other Natural-product-regulated Mirnas May Have Exosome Biog...mentioning
confidence: 99%